One piece. East blue. Volumes 4, 5, 6 - Oda, Eiichirō, 1975-; Caselman, Lance (Shonen Jump manga., 2010)
"As a child, Monkey D. Luffy dreamed of becoming King of the Pirates. But his life changed when he accidentally ate the Gum-Gum Fruit, an enchanted Devil Fruit that gave him the ability to stretch like rubber. Its only drawback? He'll never be able to swim again-- a serious handicap for an aspiring sea dog! Years later, Luffy sets off on his quest to find the "One Piece," said to be the greatest treasure in the world..." --